What are potential barriers and enablers to patient and physician participation in Canadian cell therapy trials for stroke? A stakeholder interview study. Issue 3 (19th March 2020) - Lalu, Manoj M; Foster, Madison; Presseau, Justin; Dowlatshahi, Dar; Castillo, Gisell; Cardenas, Analyssa; Tam, Whitney; Zlepnig, Jennifer; Timpson, Deborah; Dong, Yuan Yi; Juneau, Pascale; Fergusson, Dean A
Abstract : Objectives: Early phase cell therapy trials face many barriers to successful, timely completion. To optimise the conduct of a planned clinical trial of mesenchymal stem cell (MSC) therapy for chronic stroke, we sought patient and physician views on possible barriers and enablers that may influence their participation. Design: Semistructured interview study. Setting: Patients were recruited from three rehabilitation centres in Ontario, Canada; physicians were recruited from across Canada through snowball sampling. Participants: Thirteen chronic stroke patients (patients who had experienced a stroke at least 3 months prior; 10 male, 3 female) and 15 physicians (stroke physiatrists; 9 male, 6 female) participated in our interview study. Data adequacy was reached after 13 patient interviews and 13 physician interviews. Methods: Interview guides and directed content analysis were based on the Theoretical Domains Framework (TDF). Interviews were coded, and relevant themes were identified. Results: Most patients were optimistic about participating in an MSC therapy clinical trial, and many expressed interest in participating, even if it was a randomised controlled trial with the possibility of being allocated to a placebo group. However, the method of administration of cells (intravascular preferred to intracerebral) and goal of the trial (efficacy preferred to safety) may influence their intention to participate. All physicians expressed interest in screening for the trial, though many stated they were less motivated to contribute to a safety trial. Physicians also identified several time-related barriers and the need for resources to ensure feasibility. Conclusions: This novel application of the TDF helped identify key potential barriers and enablers prior to conducting a clinical trial of MSC therapy for stroke. This will be used to refine the design and conduct of our trial. A similar approach may be adopted by other investigators considering early phase cell therapy trials.